Effect of Media and Roasting Time on Quality of Brown Rice Tea (Oriza Nivara) - M. Vikri Baihaggi Vikri; Al Machfudz; Rima Azara; Syarifa Ramadhani Nurbaya (jurnal makanan tropis dan teknologi agroindustri, 2022)
This study aims to determine the interaction between the effect of roasting media and roasting time on the quality of brown rice (Oryza nivara) tea. This research was conducted at the Food Product Development and Analysis Laboratory at the Faculty of Science and Technology, University of Muhammadiyah Sidoarjo from September 2021 to December 2021. This research was conducted using a factorial randomized block design (RAK) with the first factor being the treatment of roasting media consisting of 2 levels, namely T1 (Earth Frying Pan), T2 (Metal Frying Pan) and the second factor is the roasting time consisting of 3 levels, namely S1 (Roasting Time 40 minutes), S2 (Roasting Time 50 minutes), S3 (Roasting Time 60 minutes). The results showed that there was an interaction between roasting media and roasting time on the quality of brown rice (Oryza nivara) tea color parameters using the color reader method, water content, crude fiber content and organoleptic (taste) but there was no interaction on ash content and organoleptic parameters. (color, aroma). The best parameters are found in the T1S2 treatment (Soil Frying Pan and Roasting Time 50 minutes) which shows the value of crude fiber content of 12.08%, moisture content of 2.10%, lightness value of 76.73, redness value of 1.53, yellowness value of 4.98. , 0.00% ash content, taste organoleptic 0.00, color organoleptic 0.88, aroma organoleptic 0.00.